Zoonotic Diseases in the eastern region of the Iraqi capital, between 2010-2016. Issue 1 (June 2021) - Barrak, A S; Saeed, O A; Mohammed, MTA
Abstract: There are several cases in geographical areas with zoonotic diseases before they were evident due to evolving human and climate patterns. This study was carried out to identify diagnosis, emerging diseases, as well as epidemics and pandemics affected by the zoonotic disease in Al-Ressafa, Baghdad. Data was collected between the years 2010-2016 by the Food Research Institute, Public Health Directorate, Iraq. This study targeted emerging infective diseases such as anthrax, brucellosis, cutaneous leishmaniosis, hydatidosis, rabies, and toxoplasmosis. Out of 20797 involved cases were presented, 29% emerging from zoonotic diseases. The zoonotic diseases were included parasite, viral and bacterial 75.4, 0.70, and 23.9%, respectively. Brucellosis showed high-frequency infections during March, April, and May, while cutaneous leishmaniasis occurred between February and June. The number of cases showed the male cases were 52.4 %, while the female 47.6 %. Cutaneous leishmaniasis, toxoplasmosis, and hydatidosis cases were increased at the age between 10-19 years old. In conclusion, zoonotic diseases still common on the Eastern side of Baghdad